(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the study was to compare the anti-HAV IgG and Anti-HAV IgM seropositivity in children aged 0-18 in Erzurum with studies in our country and other countries, and also to evaluate the effect of seasons on hepatitis A infection.Material and Methods: The study was conducted on the serum samples of 5086 patients aged 0-18 years, who were considered to have Hepatitis A or who applied with different complaints as a result of the examination of family physicians in Erzurum between 2015 and 2018. The results of these patients, obtained from Anti-HAV IgM and Anti-HAV IgG analysis by ELISA method in the Public Health Microbiology Laboratory, were evaluated retrospectively. Pearson chi-square test was used to analyze the categorical data such as gender, age and seasonal differences in anti-HAV IgM and Anti-HAV IgG positivity rates and p 0.05 was considered significant.Results: Anti-HAV IgG seropositivity was 69.0% (3510/5086) and Anti-HAV IgM positivity was 0.7% (33/5063). Anti-HAV IgM was positive in 1.1% of girls and 0.1% of boys. Anti-HAV IgG positivity was 89.9%, 83.3%, 62.5% 61.9% and 74.5% in the 0-3 age group, 4-7 age group, 8-11 age group, 12-15 age group and 16-18 age groups, respectively. Anti-HAV IgM positivity was 0, 0.2%, 0.2%, 1.0%, 0.9% in the 0-3 age group, 4-7 age group, 8-11 age group, 12-15 age group and 16-18 age groups, respectively. The highest anti-HAV IgM positivity was found in November (1.7%).Conclusion: Total anti-HAV IgG seropositivity rate in our province showed many similarities with studies in Turkey and developing countries. The prevalence of anti-HAV IgM was the highest in November.